STUDY OF MENARCHEAL AGE IN THREE GENERATIONS IN IRAN - "D.D. Farhud; M.S Kamali; M.Mahmoudi; R. Saffari " (Tehran University of Medical Sciences, 1990)
Three generations of women (3570 daughters, 1148 mothers and 131 grandmothers) from Tehran, Iran have been studied for menarcheal age. The results show that the age of onset of menarche has decreased in the present generation- 13.599, compared to 13.690 and 13.870 years, amount their mothers and grandmothers, respectively. These results, when compared with results obtained concerning the other Iranian groups, show the effect of both genetic and nongenetic factors on the onset of menarche.